2021
DOI: 10.1021/jacs.1c09895
|View full text |Cite
|
Sign up to set email alerts
|

“Indanonalkene” Photoluminescence Platform: Application in Real-Time Tracking the Synthesis, Remodeling, and Degradation of Soft Materials

Abstract: In this Article, we present a strategy to visually track chemically triggered covalent bonding processes in gelation, remodeling, and degradation of soft materials, i.e., hydrogels, based on a new photoluminescence platform. Initially in the development of photoluminophors named "indanonalkenes", turnon emission can be tracked and quantified in the optical reaction between a conjugate acceptor and amine derivatives. On this basis, fluorescence enhancement and mechanical changes were recorded during the gelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…S5†), through linking four-arm poly(ethylene glycol) thiol with CA-SCH 3 through thiol–thiol scrambling and high cross linking. 29 The scanning electron microscopic (SEM) images of CA-PEG are given in Fig. S6 †.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5†), through linking four-arm poly(ethylene glycol) thiol with CA-SCH 3 through thiol–thiol scrambling and high cross linking. 29 The scanning electron microscopic (SEM) images of CA-PEG are given in Fig. S6 †.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we established a photoluminescent platform based on indanonalkene luminogens (Scheme 1A). 28,29 On this basis, we employed CA-SCH 3 , an indanonalkene molecule containing a bis-vinylogous thioester group, as an amine receptor for the fluorescence detection of volatile amines via aminethiol scrambling (Scheme 1B). [30][31][32] As such, the luminescent precursor CA-SCH 3 was turned on in the presence of ammonia in both solution and solid states to generate the luminophore CA-NH 2 , exhibiting a strong green emission (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24] Through monitoring the signal changes in colorimetric and fluorometric wavelength or intensity, the presence of nerve agents can be clearly detected by chemosensors with low limit of detection (3σ/k), therefore, these methods had been widely explored in the past decades. [25][26][27][28][29][30][31][32][33][34][35] Due to the fatality of the real nerve agents, it is prohibited to investigate such reagent directly without professional training and biological safety protection third-level laboratory. Thus, common laboratories typically employed the nerve agent simulants with less toxicity, such as diethyl chlorophosphate (DCP), diethyl cyanophosphate (DCNP) to mimic G nerve agents, demeton-S-methyl (DSM) to mimic VX nerve agents as representatives for study.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the new optical methods based on chemosensors have attracted much attention due to their molecular diversity, simple operation, low cost, easy portability, real‐time detection, high sensitivity, and high selectivity [23–24] . Through monitoring the signal changes in colorimetric and fluorometric wavelength or intensity, the presence of nerve agents can be clearly detected by chemosensors with low limit of detection (3σ/κ), therefore, these methods had been widely explored in the past decades [25–35] . Due to the fatality of the real nerve agents, it is prohibited to investigate such reagent directly without professional training and biological safety protection third‐level laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reaction speed of this self-inductive cascade process should be related to the electron absorption capacity of the conjugated receptor of Meldrum acid derivatives (CA) containing two electron-absorbing groups. The optimal self-inductive cascade process suggested that CAs can be used to enhance the sensitivity of thiols, while other approaches exploit self-triggering polymers, or soft materials, which selectively release the cleavages of the end groups and trigger the sequential fragmentation to generate multiple reporters.…”
mentioning
confidence: 99%